Geochemical and physical characteristics of the sediment in Langkawi coastal waters, Malaysia - Nur Shuhada binti Muhamad Tajudin (Kulliyyah of Science, International Islamic University Malaysia, 2010)
Sediment contamination has influenced the overall quality of the aquatic environment. It serves as diffuse source of contamination to the overlying water body and slowly releasing the contaminant back into the water column. Therefore, ensuring a good sediment quality is crucial to maintain a healthy aquatic ecosystem, which enables good protection of human health and aquatic life. A geochemistry studies was conducted in the area of Langkawi coastal waters in order to access the heavy metal pollution levels in sediment. A total of 51 sediment samples were collected from 5 different zones in the area of Langkawi coastal waters. All the samples were analyzed to determine the concentration of heavy metals, sediment characteristics and total organic carbon contents. Samplings were conducted twice which were in dry (January) and wet seasons (August). The mean concentration of heavy metals studied during the dry season were 2.53±1.8% for Al, 1.024±0.22% for Fe, 221.1±101.59 μgig for Mn, 7.16±4.5 μgig for Co, 11.19±5.2 μgig for Cu, 41.87±7.3 μgig for Pb, 0.43±0.1 μgig for Cd, 68.68±18.7 μgig for Cr, and 54.504±5.45 μgig for Zn. However, during wet season, the mean concentration of Al, Fe, Mn, Co, Cu, Pb, Cd, Cr, and Zn were identified slightly higher which were 4.60±1.23μglg, l.82±0.55μglg, 254.02±74.63 μgig, 5.93±0.83μglg, 9.29±3.85μglg, 59.88±4.51 μgig, 0.40± 15μglg, 92.64±1 l.70μglg, and 57.42 ± 5.85μglg, respectively. Fe, Cu, Pb and Cr show significant of seasons to their distributions with p<0.05. However, Mn, Co, Cd, and Zn did not show any significant difference of seasons (p>0.05). The average contents of total organic carbon obtained during the dry season were 2.27± 0.59% in Zone A, 1.72±0.38% in Zone B, 2.09±0.14% in Zone C, 2.01±0.15% in Zone D, and 1.89±0.28% in Zone E. However, during wet season the average contents of the total organic carbon in Zone A, B, C, D and E were found in average of 2.38±0.44%, 2.10±0.41%, 2.43±0.52%, 2.54±0.48% and 2.53±0.38%, respectively. Enrichment factors (EFs) and Geoaccumulation Index (lgeo) were used to point out the level of pollution and the origins of the sediment. From the results, it indicates that all the heavy metals were from natural resources except for Pb and Cd which their existence might be due to the anthropogenic activities. Correlation analyses between sediment mean size and total organic carbon with regards to the concentrations of each metal show a positive but poor relationship which might be influenced by other physical and chemical parameter of the sediment.